Johannes Nádherný in the Fight Against Venereal Diseases (Theatrum historiae, 2025)
Few diseases left such a mark on the culture of the long nineteenth century as syphilis, and yet so little is known about how the people who contracted it dealt with it. This study provides a reflection on the disease through the eyes of a patient, Baron Johannes Nádherný of Borutín, whose openness in his letters and numerous descriptions of the course of his treatment have made it possible to reconstruct his life with syphilis. Nádherný’s case is contextualised by his membership of the German Society for Combatting Venereal Diseases. It was found that thanks to the discourse of the German Society Johannes had great confidence in the developing modern medicine. He took a thorough interest in his treatment, actively seeking out leading dermatovenerologists, and as a result was able to build up a wide network of the most prestigious doctors. With those doctors he consulted on the most advanced treatment options for venereal diseases and had control over his therapy.
Keywords: The Long Nineteenth Century; Social History of Medicine; Dermatovenerology; Syphilis; The German Society for Combatting Venereal Diseases